2014
DOI: 10.1155/2014/757219
|View full text |Cite
|
Sign up to set email alerts
|

Exogenous Proline and Glycine Betaine Mediated Upregulation of Antioxidant Defense and Glyoxalase Systems Provides Better Protection against Salt-Induced Oxidative Stress in Two Rice (Oryza sativaL.) Varieties

Abstract: The present study investigates the roles of exogenous proline (Pro, 5 mM) and glycine betaine (GB, 5 mM) in improving salt stress tolerance in salt sensitive (BRRI dhan49) and salt tolerant (BRRI dhan54) rice (Oryza sativa L.) varieties. Salt stresses (150 and 300 mM NaCl for 48 h) significantly reduced leaf relative water (RWC) and chlorophyll (chl) content and increased endogenous Pro and increased lipid peroxidation and H2O2 levels. Ascorbate (AsA), glutathione (GSH) and GSH/GSSG, ascorbate peroxidae (APX),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

28
191
1
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 290 publications
(223 citation statements)
references
References 77 publications
28
191
1
3
Order By: Relevance
“…It results in ion toxicity, osmotic and oxidative stress, nutritional imbalances, reduction of cell divisions and alterations in metabolic processes as photosynthesis, respiration, and disorganization of membranes of plants (Sen et al, 2002 andHasanuzzaman et al, 2014). Many investigators have reported the reduction of plant growth due to salinity stress.…”
Section: Introductionmentioning
confidence: 99%
“…It results in ion toxicity, osmotic and oxidative stress, nutritional imbalances, reduction of cell divisions and alterations in metabolic processes as photosynthesis, respiration, and disorganization of membranes of plants (Sen et al, 2002 andHasanuzzaman et al, 2014). Many investigators have reported the reduction of plant growth due to salinity stress.…”
Section: Introductionmentioning
confidence: 99%
“…Quanto a enzima de degradação, na ausência de prolina, houve uma redução na atividade da ProDH de cerca de 56% aos 7 dias (Figura 2d (Freitas, 2013) e arroz (Hasanuzzaman, et al, 2014).…”
Section: Resultsunclassified
“…This, because the salinity of soils, causing, directly or indirectly, physiological imbalances to plants (Munns, 2002). These imbalances reach most cultures for being sensitive to high concentrations of salts in the soil (Hasanuzzaman et al, 2014). Salt stress, like other environmental stresses, causes an imbalance in the appropriation of reactive oxygen species (ROS), what causes the disorderly increase of these species in the tissues of plants and can lead to severe damage to the plant (Mittler, 2002).…”
Section: Discussionmentioning
confidence: 99%